Growing Self-Organizing Maps for Firewall Log Classification in Data Streams - Giarini, Wagner Rafael; Dias, Herbert Gonçalves; Cerri, Ricardo (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2025.14281, 2025)
The growing volume of data and dynamic nature of computational networks present significant challenges to information security, particularly in data stream classification. This work investigates multiclass classification of real firewall logs from an academic environment. To address class imbalance, binary classification (allowed and denied actions) was performed. We propose an adaptation of the Growing Self-Organizing Map (GSOM) for streaming classification. Experiments were conducted in offline and online phases, evaluating three update strategies. The results demonstrate GSOM’s streaming adaptability and potential for classifying firewall logs in data streams.